PERSONALITY RIGHTS AND THE INCLUSION OF PEOPLE WITH HEARING IMPAIRMENT: CHALLENGES AND THE APPLICABILITY OF ASSISTIVE TECHNOLOGIES - Ribeiro , Daniela Menengoti Gonçalves; Katayama, Leonora Cristina dos Santos (Seven Editora, 2024)
This article explores the inclusion of people with hearing impairment, analyzing the relationship between personality rights and the application of assistive technologies. Historical evolution demonstrates significant advances, from social exclusion in Antiquity to the recognition and protection of fundamental rights in the contemporary era. Assistive technologies, such as hearing aids, cochlear implants, and transcription apps, play a crucial role in promoting autonomy and accessibility. However, obstacles such as high costs, lack of professional training and social resistance still limit the full applicability of these technologies. Brazilian legislation, especially the Brazilian Law for the Inclusion of Persons with Disabilities, and the policies of the Unified Health System (SUS), are fundamental in promoting social inclusion and guaranteeing the rights of these people. The need for a continuous and collaborative effort between governments, health institutions, educators and society is highlighted to ensure the full citizenship and active participation of people with hearing impairment. This article concludes that the promotion of personality rights and the inclusion of assistive technologies are essential for a more just, inclusive and accessible society.DOI: https://doi.org/10.56238/sevened2024.037-081